Efficacy of AccuVein to Facilitate Peripheral Intravenous Placement in Adults Presenting to an Emergency Department: A Randomized Clinical Trial. (August 2014) - Aulagnier, Jérôme; Hoc, Cécile; Mathieu, Emmanuel; Dreyfus, Jean François; Fischler, Marc; Le Guen, Morgan; Wilbur, Lee
Abstract Objectives In the emergency department (ED), intravenous (IV) catheter placement is one of the most frequent interventions and may be a real challenge in some conditions. Improvement of the success rate with new technology represents a great opportunity. This randomized controlled trial aimed to show the superiority of AccuVein to cannulate veins in adults compared to routine care. Methods After giving written consent, patients were randomized into two groups: routine IV catheter insertion or insertion guided by the AccuVein, which is a hand‐held instrument displaying laser light to optimize visualization of veins. The primary outcome was the time to successful placement of catheters. Secondary outcomes included the number of attempts, the rate of failure, technique‐related pain, occurrence of movements, and efficiency of IV cannulation as perceived by the operator when using the AccuVein device. Results are given as mean and bootstrapped 95% confidence interval (CI) and percentages. p‐values of <0.05 were considered significant. Results A total of 266 six patients were included, with 157 randomized to routine cannulation and 115 to AccuVein. Patient characteristics were similar. Time to successful placement of IV catheter (routine, 98 seconds, 95% CI = 85 to 113 seconds; and AccuVein, 119 seconds, 95% CI = 93 to 154 seconds) was not different between groups (p = 0.24). Secondary outcomes (failure and pain) did not significantly differ, except for movements, which were more frequent when using the AccuVein device (19.1% vs. 10.2%, p = 0.05). Evaluation of the AccuVein by operators was more often negative than positive. Conclusions Use of the AccuVein did not improve IV cannulation in nonselected ED patients.